2021
DOI: 10.21203/rs.3.rs-530162/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Characterization and Evaluation of Anticancer Effect of Falcaria vulgaris via Induction of Apoptosis

Abstract: Background: Apiaceae family is one of the plant families which used for medical investigation. Falcaria vulgaris is a clear example of this genus that grows in certain regions of Iran. In traditional medicine, due to the presence of coumarin and flavonoid compounds in this plant, therapeutic properties such as gastrointestinal and liver diseases, skin ulcers, gastric ulcers and intestinal inflammation have been reported. It has also been found that these compounds lead to cytotoxic effects. Objective: The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There are multiple paths through which these compounds act as antitumor agents in the human body [43], and recent clinical trials showed successful effects of terpenes on different human cancers [57]. In our research, most of the detected terpenes have previously been characterized to have antitumor effects, such as the most abundant compounds α-cadinol [58] and spathulenol that have also been described as immunomodulatory agents [59,60] and possible substances in the fight of drug resistance in cancer treatment [61]. Besides having antitumor effects, α-caryophyllene also showed immunosuppressive and analgesic properties [62].…”
Section: Health Benefits Of Terpenesmentioning
confidence: 72%
See 1 more Smart Citation
“…There are multiple paths through which these compounds act as antitumor agents in the human body [43], and recent clinical trials showed successful effects of terpenes on different human cancers [57]. In our research, most of the detected terpenes have previously been characterized to have antitumor effects, such as the most abundant compounds α-cadinol [58] and spathulenol that have also been described as immunomodulatory agents [59,60] and possible substances in the fight of drug resistance in cancer treatment [61]. Besides having antitumor effects, α-caryophyllene also showed immunosuppressive and analgesic properties [62].…”
Section: Health Benefits Of Terpenesmentioning
confidence: 72%
“…Besides having antitumor effects, α-caryophyllene also showed immunosuppressive and analgesic properties [62]. caryophyllene oxide also acts as an antitumor agent and has a cytotoxic effect on different cancer cells [61], while citronellol has been shown to be an antitumor and anti-inflammatory agent [63]. The terpene screening also showed the presence of widely researched monoterpenes, α-pinene and β-pinene that have the potential to improve human health, as they act as an antiinflammatory, antitumor, sedative, antimicrobial and antidepressant agents [17,18,64,65].…”
Section: Health Benefits Of Terpenesmentioning
confidence: 99%